Morphological, Cultural and Pathogenicity Variation of Exserohilum turcicum (Pass) Leonard and Suggs Isolates in Maize (Zea Mays L.) - Daniel Abebe,; Narong Singburaudom , (Agriculture and Natural Resources, 2006)
Surveying and collecting isolates of the fungus Exserhilum turcicum (Pass) Leonard and Suggs, the causal agent of Northern Corn Leaf Blight (NCLB), were conducted in two maize growing areas of Ethiopia in 2004 and used for studying cultural, morphological and pathogenicity varations. The results revealed that NCLB was widely distributed in almost all surveyed areas. Seventy isolates were studied for morphology and most of the conidia shapes were curved, spindle and elongated. The size of the conidia averaged 93.97 μm in length and 13.11 μm in width. The number of septa was found to range from 2 to 7. The study of cultural characteristics showed that variation existed among representatives of 28 isolates in colony growth, colony color and pigmentation. Conidial growth rate of 28 isolates was significantly different after growing the fungus on PDA. Twenty representative isolates were selected and evaluated for pathognicity on 11 seedlings maize varieties. A significant difference of disease reaction was found among tested isolates, varieties and isolates by varieties interaction. Lesion type varied in size from 0.69-2.91cm.The most virulent isolate, GOR, was found to cause disease on five varieties. Lesion size that was classified as resistance, was 0.69 to1.12cm2. Susceptible lesion size was between 1.17-2.91cm2. By applying the UPGMA in the SAHN program for cluster analysis, a pathogenicity dendogram of 20 isolates were grouped into five clusters of virulent patterns. The results of this study indicated wide variations existed among the fungi studied, therefore, the effective development of maize variety resistant to northern corn leaf blight should involve using virulent isolates, together with a mixed isolates, in order to test the disease interactions and select for resistant genotypes.